Austenite–ferrite transformation in enhanced niobium, low carbon steel. (July 2015) - Yan, P.; Bhadeshia, H. K. D. H.
Abstract : The austenite to ferrite transformation characteristics of a commercial high strength line pipe steel containing 0·05 wt-% carbon and 0·095 wt-% niobium have been rigorously studied by continuous cooling experiments in the range between 960 and 1260°C. A significant delay in the austenite to allotriomorphic ferrite transformation has been demonstrated to occur under practically relevant thermal processing conditions. The effects of prior austenite grain size and soluble niobium have been carefully evaluated and isolated and it has been concluded that the amount of niobium in solution in the austenite is primarily responsible for the retardation. Alternative hypotheses to explain the mechanism whereby niobium exerts this effect on the hardenability of steel are discussed in detail. Soluble niobium reducing the austenite grain boundary energy is argued to be the most convincing explanation of the phenomenon and a reduction of grain boundary energy of 0·286 J m −2 per wt-% of soluble niobium content has been proposed.